Hamletianism And Unmasking In German Literature Of The Xx Century - Georgievna Kolpakova, Svetlana (2017)
A large number of research works all over the world is devoted to the questions of Shakespeare study and reception of Shakespeare in Germany which once again proves high scale of his works and their influence on world artistic consciousness. The present article studies the change in the perception of the image of Hamlet in Germany in different historic periods whilst the main emphasis is put on the evolution of motives of self-condemnation and unmasking used by German writers of the XX century alongside with identification of the main character with the image of Hamlet.   the works written after World War II the motive of guilt has particularly historical interrelation. Later on Hamlet’s motive of guilt transforms into accusations (M. Walser “The Black Swan” (“Der Schwarze Schwan”, 1964)) and by the end of 1970s the central character identified with Hamlet diminishes and loses its former scale, tragedy of Hamlet’s image, pathos of unmasking and humanistic vector of development.